Clinicians need a relining or rebasing procedure - Andres Jordan Siahay; Ike Damayanti Habar (Makassar Dental Journal PDGI Makassar, 2020)
Introduction: Complete denture serves to replace natural teeth, improve aesthetics, mastication, speech function and protect periodontal tissue. Over time of its using, denture becomes loose, so it is not comfort to use. The loose of dentures can be caused by resorption of residual ridges, systemic diseases and heavy occlusion loads result in lose of retention and stability. Management of loose dentures can be performed by relining or even rebasing the dentures. Purpose: to discuss the indication and contraindication of relining and rebasing to restore the retention and stability of loose dentures. Conclusion: Clinician must understand the indications, contraindications and materials used for the relining and rebasing procedure.